Dynamics of muskox groups in northeastern Alaska - Reynolds, P. E. (Rangifer, 1993)
Group size and stability was studied in a population of re-established muskoxen (Ovibos moschatus) in northeastern Alaska by re-locating radio-collared animals. Mixed-sex groups (cows, calves, sub-adults and often adult bulls) ranged in size from 2-118 with a mean of 19.2. Almost 60 % of all mixed-sex groups contained 5¬19 individuals. Solitary cows were seen infrequently. Adult bulls were observed in mixed-sex groups, in bull groups or alone. Bull groups averaged 3.9 and ranged in size from 2 to 12. Thirty percent of all adult bulls seen outside mixed-sex groups were solitary animals. Mixed-sex groups were significantly smaller in summer/ rut Quly-September) than in midwinter Qanuary-March), spring/calving (April-June) and early winter (October-November). Mean group size was 12.2 in August compared with 23.6 in February. In August, during the rut, numbers of small groups (2-14) increased, while numbers of medium-sized (15-29) and large groups (> 29) decreased. Bull groups were significantly larger in spring/calving than during other seasons. The ratio of single bulls to bull groups was less than 0.30 in winter, increased in June, and reached a maximum during the rut in August when more than 2 single bulls were seen for every bull group. Group size and individuals within a group changed frequently. This fluid social system provides a balance between protection from predators, efficient food acquisition and the formation of harems during the rut.